a3-3=-32

To remove the radical on the left side of the equation, square both sides of the equation.

a3-32=(-32)2

Multiply the exponents in ((a3-3)12)2.

Apply the power rule and multiply exponents, (am)n=amn.

(a3-3)12⋅2=(-32)2

Cancel the common factor of 2.

Cancel the common factor.

(a3-3)12⋅2=(-32)2

Rewrite the expression.

(a3-3)1=(-32)2

(a3-3)1=(-32)2

(a3-3)1=(-32)2

Simplify.

a3-3=(-32)2

Raise -32 to the power of 2.

a3-3=1024

a3-3=1024

Move all terms not containing a to the right side of the equation.

Add 3 to both sides of the equation.

a3=1024+3

Add 1024 and 3.

a3=1027

a3=1027

Multiply both sides of the equation by 3.

3⋅a3=3⋅1027

Simplify both sides of the equation.

Cancel the common factor of 3.

Cancel the common factor.

3⋅a3=3⋅1027

Rewrite the expression.

a=3⋅1027

a=3⋅1027

Multiply 3 by 1027.

a=3081

a=3081

a=3081

Exclude the solutions that do not make a3-3=-32 true.

No solution

Solve using the Square Root Property square root of a/3-3=-32